Pengukuran Kepuasan dan Kualitas Pelayanan terhadap Konsumen Jasa Transportasi Kereta Api - Febriyanti, Adelia; Setyawan, Anton Agus (Jurnal Informatika Ekonomi Bisnis, 2024)
This research aims to analyze the measurement of customer satisfaction and service quality in the context of rail transportation services. The theory used in this research is the Servqual theory, which emphasizes five dimensions of service quality, namely concrete evidence, reliability, responsiveness, assurance, and empathy. The research method applied was a survey design involving 140 respondents who used rail transportation services in Surakarta. Sampling was carried out using a purposive sampling method, with the criteria being that respondents were less than 40 years old and had used train transportation services at least 4 times in the last year. The research results show that there is a positive influence of employee service behavior orientation on service quality with a T statistic of 7.041 (>1.96) and a P value of 0.000 (<0.05) and a positive influence of physical facilities on service quality with a t statistic of 4.860 (>1.96) and P value 0.000 (<0.05). Apart from that, service quality has also been proven to have a positive effect on consumer satisfaction with a T statistic of 12.942 (>1.96) and a P value of 0.000 (<0.05). The implication of these findings is that it is important for rail transportation service companies to pay attention to employee behavior and physical facilities as an effort to improve service quality, which in turn can increase consumer satisfaction and the competitiveness of transportation service companies.